Stimulation method and individual health index study for real-time cardiovascular and autonomic nervous system reactivity analysis using PPG signal. (July 2022) - Kim, Daechang; Lee, Younju; Jeong, Jaehoon; Kim, Sungmin
Highlights: The change from a sit to a stand position can be one way to observe the reactivity and relationship of the autonomic nervous system and the cardiovascular system in daily life. When changes in the cardiovascular system occur rapidly, the sympathetic maintains highly active. This period is similar to the time the cardiovascular system responds to changes. In the standing position, the activity of parasympathetic nerves acting on the cardiovascular system is increased because the baroreceptors are stimulated through breath. Abstract: Homeostasis in a healthy heart is maintained through the interaction of the autonomic nervous system (ANS) with the cardiovascular system (CS) in response to changes in the environment. However, the problem of the ANS and CS reactivity caused by aging and chronic disease increases the risk of fatal heart disease and negatively affects an individual's health. Therefore, we propose a method and heart rate variability (HRV) index that can continuously monitor the reactivity of ANS and CS in daily life. To analyze real-time changes in ANS and CS of a total of 22 subjects, HRV was induced by changing the posture from a sitting position to a standing position while measuring photoplethysmogram. As a result, it was confirmed that the HRV changed from 0.75 ± 0.11 s to 0.65 ± 0.10 s (P < 0.05) had a change value similar to the method used in clinical. Physiological ANS activity can be confirmed through the standard deviation 1 (SD1) and 2, and ANS activity reflected in CS can be obtained through the standard deviation of all NN intervals (SDNN) and the root mean square of successive heartbeat interval differences (RMSSD) analysis. As a result of analyzing the two values, the 5-minute average SD1/RMSSD is identified as an indicator that can confirm the function of the baroreceptors indicative of CS reactivity. In addition, we propose a real-time SDNN as an index that can check the term of the activated ANS in response to a sudden CS change.